Introducing Foundry-Compatible SiC and GaN Trench Processing Technologies for Reliable Automotive Application - BEN JONES (Materials Science Forum, 2022)
In this paper we report the progress of our SiC trench etch development using enhanced ICP-based etch technology. Computer modelling of the electric field strength in the gate oxide as a function of corner geometry was used to illustrate trench corner rounding as an effective method to avoid to high gate oxide field strengths. This is an effort to examine a major ongoing issue in device reliability, and to govern future device design.